GAMBARAN PENGETAHUAN IBU HAMIL TENTANG ANEMIA DI WILAYAH KERJA PUSKESMAS SAYURMATINGGI KECAMATAN SAYURMATINGGI KABUPATEN TAPANULI SELATAN TAHUN 2023 - Rangkuti, Nur Aliyah; Harahap, Cory Linda Futri; Rangkuti, Juni Andriani; Harahap, Mei Adelina; Nasution, Ayannur; Ritonga, Nefonavratilova; Ramadhini, Delfi; Yuni Aflah; Deliana Tarigan (Universitas Aufa Royhan, 2023)
Anemia is a condition where the hemoglobin (Hb) level in the blood is less than normal, based on age group, gender and pregnancy. Anemia in pregnancy causes hemoglobin levels below 11 gr% in the first and third trimesters or hemoglobin levels <10.50 to 11.00 gr/dl. Anemia is an important factor in pregnancy because it is associated with morbidity or mortality in the mother and fetus. Anemia in pregnancy is a problem because it reflects the socio-economic welfare of society and has a huge influence on the quality of human resources. Anemia in pregnant women is called